Sustainability consciousness of pre-service English teachers - Hui Li (Discover Sustainability)
Abstract Purpose This study explores the state of pre-service English teachers’ sustainability consciousness and the influencing factors. Design/methodology/approach The researcher employed a quantitative research design to examine Chinese pre-service English teachers’ sustainability consciousness. Data were collected using a survey instrument administered to 1142 participants, comprising 784 undergraduate students enrolled in an English for future teachers program and 658 undergraduates from other majors at the same university. The research aimed to assess comprehensive outcomes, investigate differences based on variables, and analyze interconnections among subdimensions. Findings The results showed that Chinese pre-service English teachers demonstrated a favorable attitude toward sustainable development, yet their actual behavior toward sustainable development was relatively low. The variables such as gender, major, educational level, type of leisure activities, and training significantly impacted the acquisition of the mentioned competencies. Furthermore, studies have shown that knowledge and attitude correlate significantly and positively with behavior. Originality/value This research contributes to a broader debate on measuring the sustainability consciousness of pre-service English teachers. Additionally, it underscores the importance of incorporating sustainability education into university teacher education programs.